Anesthetic effects of different volumes of lidocaine for spermatic cord block in cattle - Neves, Ana C.; Santos Júnior, Juracy CB.; Marucio, Rodrigo L.; Midon, Monica [UNESP]; Luna, Stelio PL. [UNESP] (Elsevier, 2017)
Objective To evaluate three volumes of lidocaine for spermatic cord block to perform castration in cattle. Study design Randomized blinded clinical study. Animals Thirty mixed-breed Nellore cattle, aged 28–40 months and weighing 395 ± 21 (352–452) kg [mean ± standard deviation (range)]. Methods Cattle were restrained in a chute and allowed to stand without sedation. Three milliliters of 2% lidocaine without epinephrine were infiltrated subcutaneously at each site of scrotal incision in all animals. The animals were allocated to three groups of 10 animals each. Lidocaine 2% was injected into each spermatic cord using a volume of 2, 3 or 4 mL in groups A, B, or C, respectively. The total volumes of lidocaine used were 10, 12, and 14 mL in groups A, B, and C, respectively. The duration of surgery and the retraction of the testicle (scored as positive or negative according to retraction of the testicle) during the procedure were recorded. The data were statistically analyzed by one-way ANOVA followed by Tukey's and chi-square tests. Differences were considered significant when p < 0.05. Results The mean surgical time was shorter in group C than in groups A and B (p < 0.001). In groups A, B and C, 90%, 60% and 10% of the animals showed retraction of the testicle, respectively. Fewer animals retracted the spermatic cord in group C than in group A (p = 0.002) and B (p = 0.02). Conclusions and clinical relevance Optimal spermatic cord block was achieved by injection of 4 mL of 2% lidocaine 5 minutes before castration and following incisional infiltration of lidocaine, in adult cattle weighing about 400 kg.
Keywords: analgesia; castration; cattle; lidocaine; orchidectomy; pain